THE EFFECT OF USING CARICATURE MEDIA ON THE SKILLS OF WRITING ANECDOTAL TEXTS OF NINTH GRADE SENIOR HIGH SCHOOL ON LAREH SAGO HALABAN - Neneng Wahyuni; Wirda Linda; Wangiman Wangiman; Dina Istiqomah; Elsa Saputri (Lembaga Penelitian dan Pengabdian Kepada Masyarakat STKIP Ahlussunnah, 2023)
This research uses quantitative research with experimental methods. The design of this study used The Randomized Posttest Only Control Group. The population of this study amounted to 238 students with sampling using purposive sampling. The research instrument is a test. The test used is a performance test that is useful for measuring anecdotal text writing skills. Data analysis can be concluded that the results of the t-test (t-test) in the experimental class prove tcount = 7.5188 with ttable = 2.064, because tcount is greater than ttable (7.5188 > 2.064), then Ha (alternative hypothesis) is accepted. Furthermore, the results of the t-test (t-test) in the control class prove that tcount = 2.9176 with ttable = 2.064, because tcount is greater than ttable (2.9176 > 2.064), then Ha (alternative hypothesis) is accepted. The results of the t-test (t-test) are the results of the comparison of tcount = 3.2435 with ttable = 2.021, because tcount is greater than ttable (3.2435 > 2.021), then Ha (alternative hypothesis) is accepted. The conclusion of the study, anecdotal text writing skills have a stronger effect using caricature media than without using caricature media.